Preparation and Characterization of Ultrasonically Modified Peanut Protein–Guar Gum Composite Emulsion Gels for 3D Printing - Hong-Yan Yan; Shao-Bing Zhang (Gels)
This study aimed to prepare ultrasonically modified peanut protein–guar gum composite emulsion gels for 3D printing. The composition of the composite emulsion gels was determined in single-factor and orthogonal experiments. The results revealed that the optimal composite emulsion gels consisted of 6% peanut protein, 50% oil and 0.2% guar gum. After crushing pretreatment for 45 s, the printing deviation of the composite emulsion gels was reduced to 8.58 ± 0.20%. Moreover, after ultrasonic treatment (200 W for 20 min) of peanut proteins, the obtained composite emulsion gels presented the highest yield stress, hardness and G’ values, as well as a denser and more homogeneous microstructure. After protein ultrasonic modification (200 W or 600 W for 20 min), the printing accuracy and self-supporting properties of the composite emulsion gels for printing complex shapes significantly improved, which was attributed to their stronger textural and rheological properties; however, ultrasonically modified peanut protein–guar gum composite emulsion gels were not suitable for printing products with smooth surfaces.